PENGARUH PELATIHAN TEKNIS PERPAJAKAN, PROFESIONALISME, AKUNTABILITAS, PERENCANAAN PEMERIKSAAN PAJAK, BATASAN WAKTU DAN KONFLIK PERAN TERHADAP KINERJA PEMERIKSA PAJAK (Studi Empiris pada Pemeriksa Pajak yang Terdaftar di KPP se Kota Pekanbaru) - Safitri, Devi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
The aim of this study was to examine the effect of taxation technical training, profesionalisme, accountability, planning of taxes inspection, deadline, and Role Conflict againts taxesâs inspectioning. Independent variables used in this study are taxation technical training, profesionalisme, accountability, planning of taxes inspection, deadline,and Role Conflict, while dependent variables in this study is the Performance Of Tax Inspectors. The populations used in this study are all of coming from pekanbaruâs taxes attandace where the total sample is used by 56 taxes employes that registered as taxes inspectoring at pekanbaruâs taxes attandance office. The sampling thecnique in which the number of observation use purposive method. The method of analysis of this study using multiple regression analysis with help of softwere SPSS version 20,0. This study used classic assumption test composed of normality test, heteroskedasity test, autocorrelation test, and multi collinearity test. While hypothesis test is down with t test. The results of this study indicate that all independent variables are taxation technical training, profesionalisme, accountability, planning of taxes inspection, and Role Conflict affect the Performance Of Tax Inspectors on the level of significant (Î±) <0,05. But the independent variable deadline cant affect the Performance Of Tax Inspectors on the level of significant (Î±) < 0,05, The coefficient of determination as big as 98,5% indicates that 98,5% of the variations that occur in the Of Tax Inspectors is affected by are taxation technical training, profesionalisme, accountability, planning of taxes inspection, deadline,and Role Conflict. While the rest of 1,5% were affected by other variabel that were not performed in this study.